GROWTH AND NUTRIENT DIGESTIBlLITY OF JELAWAT (Leptobarbus hoeveni) FRY FED WITH VARIOUS DIETARY PROTEIN LEVELS - Mas Tri Djoko Sunarno (Indonesian Fisheries Research Journal, 2002)
A growth and nutnent dtgesttbility study was executed for jelawat fry in the laboratory. The fry (40 day-old) were reared in 9 aquariums of 37.5L water volume at 30 per tank and fed an isocaloric diet(42kcal) contatning 3 dietary protein levels (33, 40, 47%) at 10% of body weigh tadayfor 49 days. Biomass was weighed fortnightly.